2007
DOI: 10.1097/jcp.0b013e31814ce50d
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Extended-Release Naltrexone in Alcohol-Dependent Patients Who Are Abstinent Before Treatment

Abstract: Extended-release naltrexone (XR-NTX) is a once-a-month injectable formulation that is Food and Drug Administration-approved for the treatment of alcohol dependence in patients able to abstain from alcohol before treatment initiation. This paper presents the results of an analysis of efficacy data from a subgroup of patients with 4 days or more of voluntary abstinence before treatment initiation (n = 82) on a wide range of drinking-related outcomes. In these patients, all of whom received counseling, the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 16 publications
4
85
2
1
Order By: Relevance
“…Studies of the effi cacy of injectable naltrexone in treating AUD patients indicate that it reduces drinking days, median drinks per day, and number of heavy drinking days and increases abstinence rates, percentage of days abstinent, length of continuous abstinence, time to fi rst drink, and time to fi rst heavy drinking day (Garbutt et al, 2005;Gastfriend et al, 2005;Kranzler et al, 2004;Lee et al, 2012;O'Malley et al, 2007). Recent meta-analyses of studies assessing injectable naltrexone's effectiveness indicate that its use in AUD patients is linked to a reduction in heavy drinking days (Jonas et al, 2014), longer refi ll persistence, and longer medication persistence compared with acamprosate (Campral) and tablet naltrexone (Hartung et al, 2014).…”
mentioning
confidence: 99%
“…Studies of the effi cacy of injectable naltrexone in treating AUD patients indicate that it reduces drinking days, median drinks per day, and number of heavy drinking days and increases abstinence rates, percentage of days abstinent, length of continuous abstinence, time to fi rst drink, and time to fi rst heavy drinking day (Garbutt et al, 2005;Gastfriend et al, 2005;Kranzler et al, 2004;Lee et al, 2012;O'Malley et al, 2007). Recent meta-analyses of studies assessing injectable naltrexone's effectiveness indicate that its use in AUD patients is linked to a reduction in heavy drinking days (Jonas et al, 2014), longer refi ll persistence, and longer medication persistence compared with acamprosate (Campral) and tablet naltrexone (Hartung et al, 2014).…”
mentioning
confidence: 99%
“…Another trial found that injectable naltrexone increased time to first drinking day but did not have an effect on time to first heavy drinking day (Kranzler et al, 2004). One trial found that only patients who were abstinent from alcohol before treatment showed a benefit (O'Malley et al, 2007). Furthermore, a recent trial demonstrated fewer drinks per day, fewer drinking days per month and decreased rates of heave drinking days (Lee et al, 2010) One of the largest trials evaluating the efficacy of injectable naltrexone was the COMBINE trial, which evaluated the effect of injectable naltrexone in combination with behavioral intervention, acamprosate, or both.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the use of naltrexone in an extendedrelease intra-muscular (i.m.) depot formulation (Vivitrol  ) is more effective in patients who are able to abstain from drinking prior to treatment (O'Malley et al, 2007;Pettinati et al, 2009). Taken together, treatment with naltrexone appears to have the most consistent effects on drinking outcomes in subjects with A118G mutation.…”
Section: Clinical Studies With Naltrexonementioning
confidence: 99%